Digital Tourism Revenue Monitoring Framework for Heritage Destinations in Baubau - Aulia Nahda Octavia; Nur Qalbi Hafidzah M; Arsan Limowa; Moh. Zidik Saputra (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study develops a digital tourism revenue monitoring framework for heritage destination management in Baubau City, Indonesia. Although tourism retribution from government-managed attractions has exceeded local revenue targets, the field evidence indicates that revenue governance still depends on conventional collection, recording, verification, and treasury deposit procedures. Using a descriptive qualitative design, this study analyzed field interviews, government documents, tourism revenue targets, visitor-related infrastructure data, and the institutional roles of the Tourism and Culture Office of Baubau City. The findings show that Benteng Keraton Buton and Batu Sori are the only tourism assets directly managed by the local government, while other destinations rely on community management. Tourism revenue reached 120% of the 2024 target and 111.11% of the 2025 target, supported by retribution tariffs, destination maintenance, cultural events, and digital promotion. However, the current system lacks integrated data capture, real-time revenue dashboards, visitor segmentation, digital payment traceability, and automated monitoring of collection-to-deposit flows. The proposed framework integrates destination-level retribution input, digital payment options, collector verification, treasury reconciliation, visitor category data, and managerial dashboards for revenue forecasting and anomaly detection readiness. The study contributes to digital business-oriented tourism governance by positioning local tourism revenue not only as a financial outcome but also as a data asset for accountability, planning, and destination competitiveness.